Janus Kinase inhibitors in dermatology: a review - Bárbara Vieira-Granja; Sofia Magina (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Janus Kinases (JAKs) are a subset of cytoplasmic protein tyrosine kinases (TYK), crucial for the initiation of signaling pathways activated by cytokines through phosphorylation and activation of the signal transducer and activator of transcription (STAT) proteins. Selective JAK inhibitors can simultaneously block the function of multiple cytokines and, consequently, the transcription of genes responsible for inflammation and the control of innate and adaptative immunity. These molecules play a foundational role in the underlying pathogenesis of multiple immune-related conditions such as atopic dermatitis (AD), rheumatoid arthritis, psoriatic arthritis, inflammatory bowel disease, and others. There is growing evidence that JAK inhibitors are efficacious in AD, alopecia areata (AA), psoriasis (PSO), and vitiligo. Additional evidence suggests that JAK inhibition may be broadly useful in dermatology, with early reports of efficacy in other conditions. They can be administrated orally; however, the concern for side effects has prompted the investigation into topical preparations that appear to be safe and well-tolerated and can be a promising alternative to oral formulations.